2021
DOI: 10.7717/peerj.11902
|View full text |Cite
|
Sign up to set email alerts
|

Geographic disparities and socio-demographic predictors of pertussis risk in Florida

Abstract: Background Pertussis is a toxin-mediated respiratory illness caused by Bordetella pertussis that can result in severe complications and death, particularly in infants. Between 2008 and 2011, children less than 3 months old accounted for 83% of the pertussis deaths in the United States. Understanding the geographic disparities in the distribution of pertussis risk and identifying high risk geographic areas is necessary for guiding resource allocation and public health control strategies. Therefore, this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Misperceptions about lower disease risk in rural areas may be one reason for decreased parental concerns regarding disease severity. However, VPD outbreaks cluster geographically [ 56 – 59 ] in both urban [ 58 ] and rural environments [ 57 , 60 ]. A recent study in Florida found that even though more pertussis cases were identified in urban areas, the risk of pertussis was higher in rural counties compared to urban counties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misperceptions about lower disease risk in rural areas may be one reason for decreased parental concerns regarding disease severity. However, VPD outbreaks cluster geographically [ 56 – 59 ] in both urban [ 58 ] and rural environments [ 57 , 60 ]. A recent study in Florida found that even though more pertussis cases were identified in urban areas, the risk of pertussis was higher in rural counties compared to urban counties.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Florida found that even though more pertussis cases were identified in urban areas, the risk of pertussis was higher in rural counties compared to urban counties. Indeed, given the ample evidence that lower vaccination coverage leads to higher VPD risk, it was suggested that rural counties in Florida had higher disease risk due to lower vaccination coverage [ 58 ]. Misperceptions that rurality is associated with less disease risk should be addressed in targeted community interventions.…”
Section: Discussionmentioning
confidence: 99%